Implementation Of Wound Care Education In A Diabetic Ulcer Patient With Knowledge Deficits - Oktavianti, Riska Fitri; Fitriani, Ade; Lismayanti, Lilis (KIAN JOURNAL, 2025)
Background: Diabetes mellitus is a metabolic disease that can cause various complications, one of which is diabetic ulcers. These ulcers occur due to impaired circulation and peripheral neuropathy which causes wounds to heal. In an effort to manage diabetic ulcers, an educational approach is needed to increase patient awareness of the importance of proper wound care and infection prevention efforts. Nursing education plays an important role in helping patients understand the relationship between uncontrolled blood glucose levels and the impaired wound healing process. Increased patient understanding is expected to encourage behavioral changes in self-care and improve compliance with medical recommendations. Objectives: This case study aims to evaluate the implementation of wound care education with impaired knowledge deficits in diabetic ulcer patients through a nursing approach. This research method is in the form of a case study using a descriptive Method: with a research design using a nursing care approach which includes assessment, nursing diagnosis, nursing intervention, nursing implementation, nursing evaluation which is carried out for 3 meetings at the patient's home in the rose ray neighborhood, RT. 001 RW. 008, cigembor village, ciamis sub-district Results: After implementing education for three meetings, the results showed that the client's understanding of wound care had increased. The client showed the ability to recite the correct wound care steps, recognize signs of infection, and understand the importance of controlling blood glucose levels in accelerating wound healing. The family also began to play an active role in assisting the wound care process at home. Conclusion: The implementation of wound care education can improve client knowledge and skills in caring for diabetic ulcers to prevent infection. This education can be an important part of promotive and preventive nursing interventions to support the wound healing process and prevent further complications.